2005
DOI: 10.1093/jn/135.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Ferrous Sulfate Is More Bioavailable among Preschoolers than Other Forms of Iron in a Milk-Based Weaning Food Distributed by PROGRESA, a National Program in Mexico,

Abstract: After 1 y of distributing a milk-based fortified weaning food provided by the Mexican social program PROGRESA, positive effects on physical growth, prevalence of anemia, and several vitamin deficiencies were observed. There was no effect on iron status, which we hypothesized was related to the poor bioavailability of the reduced iron used as a fortificant in PROGRESA. The objective of this study was to compare the iron bioavailability from different iron sources added as fortificants to the weaning food. Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 33 publications
1
40
3
Order By: Relevance
“…These results thus differ from earlier studies in infants in Bangladesh (Sarker et al, 2004) and Mexico (Perez-Exposito et al, 2005), which reported that iron absorption from complementary foods fortified with ferrous fumarate was only one-third of that from ferrous sulfate. There are several potential explanations for these differences.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results thus differ from earlier studies in infants in Bangladesh (Sarker et al, 2004) and Mexico (Perez-Exposito et al, 2005), which reported that iron absorption from complementary foods fortified with ferrous fumarate was only one-third of that from ferrous sulfate. There are several potential explanations for these differences.…”
Section: Discussioncontrasting
confidence: 99%
“…The results from the Bangladesh study (Sarker et al, 2004) would be most consistent with this hypothesis, Relative bioavailability of ferrous fumarate M Harrington et al as all the Bangladeshi children were iron-deficient anemic, compared with none in the present study. In the study by Perez-Exposito et al (2005), 11% of the Mexican children were anemic and 30% were iron deficient compared with iron deficiency in 39% of women, 6% of infants and 5% of children in the present study. The absolute absorption of iron from the iron fortified test meals in the present study was higher in women than in infants or young children.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Previous evidence suggests that different iron salts show similar tolerability in clinical use. [22] In two studies comparing the absorption of ferrous sulfate and ferrous fumarate from fortified milk-based drinks, one study found that ferrous sulfate was better absorbed than ferrous fumarate, [23] while absorption of ferrous sulfate and ferrous fumarate did not differ significantly in the second study. [24] Given the significant effects that the type of salt may have on in vitro dissolution, ferrous sulfate-containing supplements such as Folifer Ò may therefore be a better choice for iron/folic acid supplementation in individuals at risk of iron/folate deficiencies, such as pregnant and lactating women.…”
Section: Discussionmentioning
confidence: 99%